Treatment of Lactic Acidosis with Dichloroacetate in Dogs - Robert Park; Allen I. Arieff; William Leach; Virginia C. Lazarowitz (The Journal of Clinical Investigation, 1982)
Lactic acidosis is a clinical condition due to accumulation of H+ ions from lactic acid, characterized by blood lactate levels >5 mM and arterial pH <7.25. In addition to supportive care, treatment usually consists of intravenous NaHCO3, with a resultant mortality >60%. Dichloroacetate (DCA) is a compound that lowers blood lactate levels under various conditions in both man and laboratory animals. It acts to increase pyruvate oxidation by activation of pyruvate dehydrogenase. We evaluated the effects of DCA in the treatment of two different models of type B experimental lactic acidosis in diabetic dogs: hepatectomy-lactic acidosis and phenformin-lactic acidosis. The metabolic and systemic effects examined included arterial blood pH and levels of bicarbonate and lactate; the intracellular pH (pHi) in liver and skeletal muscle; cardiac index, arterial blood pressure and liver blood flow; liver lactate uptake and extrahepatic splanchnic (gut) lactate production; and mortality. Effects of DCA were compared with those of either NaCl or NaHCO3. The infusion of DCA and NaHCO3, delivered equal amounts of volume and sodium, although the quantity of NaHCO3 infused (2.5 meq/kg per h) was insufficient to normalize arterial pH. In phenformin-lactic acidosis, DCA-treated animals had a mortality of 22%, vs. 89% in those treated with NaHCO3. DCA therapy increased arterial pH and bicarbonate, liver pHi and cardiac index, with increased liver lactate uptake and a fall in blood lactate. With NaHCO3 therapy, there were decrements of cardiac index and liver pHi, with an increase in venous pCO2 and gut production of lactate. Dogs with hepatectomy-lactic acidosis were either treated or pretreated with DCA. Treatment with DCA resulted in stabilization of cardiac index, a fall in blood lactate, and 17% mortality. NaHCO3 was associated with a continuous decline of cardiac index, rise in blood lactate, and 67% mortality. In dogs pretreated with NaCl, mortality was 33%, but all dogs pretreated with DCA survived. Dogs pretreated with DCA also had lower blood lactate and higher arterial pH and bicarbonate than did those pretreated with NaCl. Thus, in either of two models of type B experimental lactic acidosis, treatment with DCA improves cardiac index, arterial pH, bicarbonate and lactate, and liver pHi. The mortality in dogs with type B lactic acidosis was significantly less in DCA-treated animals than in those treated with other modalities.